2008
DOI: 10.1186/1471-2164-9-608
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide (LPS) potentiates hydrogen peroxide toxicity in T98G astrocytoma cells by suppression of anti-oxidative and growth factor gene expression

Abstract: Background: Lipopolysaccharide (LPS) is a cell wall component of Gram-negative bacteria with proved role in pathogenesis of sepsis. Brain injury was observed with both patients dead from sepsis and animal septic models. However, in vitro administration of LPS has not shown obvious cell damage to astrocytes and other relative cell lines while it does cause endothelial cell death in vitro. These observations make it difficult to understand the role of LPS in brain parenchymal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
3
0
1
Order By: Relevance
“…Our discovery that expression of Cytochrome b561, an abundant transmembrane protein from neuroendocrine vesicles is selectively increased in castration recurrent tumors of CWR22 tumor model is an important observation. Based on the data presented here, altered Cytochrome b561 expression does not appear to represent neuro-endocrine cells per se which is reminiscent of earlier and recent observations, where Cytochrome b561 is expressed in tumor cells lines of diverse tissue types [12,21,22]. On the basis of accumulating evidence of sustained androgen receptor signaling during the progression of CaP in response to androgen ablation [2,23], we propose that AR signaling activation may lead to the Cytochrome b561 expression in CRPC.…”
Section: Discussionsupporting
confidence: 53%
“…Our discovery that expression of Cytochrome b561, an abundant transmembrane protein from neuroendocrine vesicles is selectively increased in castration recurrent tumors of CWR22 tumor model is an important observation. Based on the data presented here, altered Cytochrome b561 expression does not appear to represent neuro-endocrine cells per se which is reminiscent of earlier and recent observations, where Cytochrome b561 is expressed in tumor cells lines of diverse tissue types [12,21,22]. On the basis of accumulating evidence of sustained androgen receptor signaling during the progression of CaP in response to androgen ablation [2,23], we propose that AR signaling activation may lead to the Cytochrome b561 expression in CRPC.…”
Section: Discussionsupporting
confidence: 53%
“…Independent of the LPS concentration [0, 2.5, 5, 10, and 100 μg/mL], there was no cytotoxic effect on cells isolated from the dermis and epidermis of the equine hoof. On the one hand, previous studies showed no cytotoxic effect of LPS on equine macrophage cell line (eCAS) [ 33 ] or astrocytes cell line [ 34 ] and even demonstrated an increased proliferation of human fibroblasts and keratinocytes after LPS treatment [ 35 ]. On the other hand, it was reported that LPS inhibited the cell growth of mesenchymal cell lines, epithelial cells and significantly decreased the viability of mouse macrophage cell line (RAW 264.7) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…T98G cells were grown as monolayer cultures in Dulbecco’s Modified Eagle’s Medium (DMEM, Gibco), supplemented with 10% fetal bovine serum (FBS, Gibco), 100 IU/ml penicillin and 100 μg/ml streptomycin (Gibco) [35,36]. All cells were grown at 37°C in a humidified atmosphere of 95% O 2 and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%